Multi-fuzzy sets and their correspondence to other sets - Sebastian, Sabu; John, Robert (Kyung Moon Sa. Co., 2016)
This paper discusses the properties of multi-fuzzy sets with product order and dictionary order on their membership functions. In particular the relationship between multi-fuzzy sets and other sets such as intuitionistic fuzzy sets, type-2 fuzzy sets, multisets and fuzzy multisets are studied.